2018
DOI: 10.1038/s41467-018-02932-7
|View full text |Cite
|
Sign up to set email alerts
|

Stimuli-responsive hydroxyapatite liquid crystal with macroscopically controllable ordering and magneto-optical functions

Abstract: Liquid crystals are mostly formed by self-assembly of organic molecules. In contrast, inorganic materials available as liquid crystals are limited. Here we report the development of liquid-crystalline (LC) hydroxyapatite (HAp), which is an environmentally friendly and biocompatible biomineral. Its alignment behavior, magneto-optical properties, and atomic-scale structures are described. We successfully induce LC properties into aqueous colloidal dispersions of rod-shaped HAp by controlling the morphology of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
108
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(112 citation statements)
references
References 55 publications
3
108
1
Order By: Relevance
“…However, when we moved the magnet to a different side of the vial after completion of the phase separation (this changed the direction of the magnetic field), the chiral nematic bands in the macroscopic liquid crystalline phase were not reoriented parallel to the new magnetic field direction even after 24 h, although the bulk isotropic and liquid crystalline phases immediately moved in several seconds (i.e., the isotropic phase was attracted to the side closer to the magnet, whereas the liquid crystalline phase moved to the other side farther from the magnet) to minimize the magnetic potential energy. This mechanism is intrinsically different from the magnetic alignment of liquid crystals reported by Gray and others, [39][40][41][42][43] who showed that the chiral nematic bands of tactoids are directly aligned perpendicular to a very strong magnetic field (about 7 tesla) as a result of the diamagnetic or paramagnetic anisotropy of the mesogens themselves. Vignolini elegantly applied that concept to control the helical pitches and optical properties of chiral nematic CNC films by applying weak magnetic fields to drying CNC dispersions.…”
Section: Unidirectional Phase Separation and Alignment Of Chiral Nemacontrasting
confidence: 61%
“…However, when we moved the magnet to a different side of the vial after completion of the phase separation (this changed the direction of the magnetic field), the chiral nematic bands in the macroscopic liquid crystalline phase were not reoriented parallel to the new magnetic field direction even after 24 h, although the bulk isotropic and liquid crystalline phases immediately moved in several seconds (i.e., the isotropic phase was attracted to the side closer to the magnet, whereas the liquid crystalline phase moved to the other side farther from the magnet) to minimize the magnetic potential energy. This mechanism is intrinsically different from the magnetic alignment of liquid crystals reported by Gray and others, [39][40][41][42][43] who showed that the chiral nematic bands of tactoids are directly aligned perpendicular to a very strong magnetic field (about 7 tesla) as a result of the diamagnetic or paramagnetic anisotropy of the mesogens themselves. Vignolini elegantly applied that concept to control the helical pitches and optical properties of chiral nematic CNC films by applying weak magnetic fields to drying CNC dispersions.…”
Section: Unidirectional Phase Separation and Alignment Of Chiral Nemacontrasting
confidence: 61%
“…The thermogravimetric analysis (TGA) result implies that the HAP content in the hybrid is 25.4 wt%, and the organic content is 74.6 wt% (Figure S6, Supporting Information). The oriented arrangement is an important characteristic of the resulting PVA/Alg/HAP hybrid macrofiber, which is demonstrated by the brilliant color observed under cross‐polarized light caused by the birefringence phenomenon exhibited by the ordered HAP nanocrystal (Figure h) . The PVA/Alg hybrid film was used as a control, and after achieving tensile fracture with a strain of 200%, the control cannot exhibit a brilliant color under cross‐polarized light due to the lack of an ordered crystal structure (Figure S7, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the normalized birefringence intensity of the pristine gel fiber at v 2 = 3 v 1 was 1.7-fold lower than that of the modified GO gel fiber at v 2 = 4 v 1 , indicating that the pristine gel fiber had a relatively low degree of orientation (fig. S5D) ( 16 ). Together, these results indicated that highly oriented gel fibers could not be obtained using the CaCl 2 -only coagulation solution because the pristine gel was sensitive to high-speed mechanical drawing, which is essential to obtain highly aligned LC domains.…”
Section: Resultsmentioning
confidence: 99%